Fostering student engagement during teaching practicum: pre-service EFL teachers’ strategies - Salsabila, Iqlil (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
The lack of student engagement greatly influences the implementation of the learning process. This is very important because it refers to the pre-service teacher’s ability to manage the class so that it runs effectively and involves all students. This study explores the strategies pre-service teachers use to increase student engagement. This research was designed with a case study approach. Four pre-service EFL teachers were selected as participants in the research. In collecting data, the researcher used semi-structured interview techniques and observations through video recordings of teaching carried out by each participant. The data were analyzed using thematic analysis. The findings revealed that there were six strategies used to increase student engagement during teaching practicum, including measuring student engagement, establishing good communication between pre-service teachers and students, balancing structure and student autonomy through cooperative learning methods, promoting digital media as an innovation in the learning process, providing evaluation questions, and increasing the engagement of students with exciting activities. This study concludes with pedagogical implications for how pre-service teachers can use strategies to increase student engagement in English learning during teaching practicum.